Проблеми створення штучного інтелекту та філософія свідомості - Темчур, К. О. (ХНУРЕ, 2019)
The article discusses possibility of existence of consciousness in artificial intelligence. It is argued that researchers and developers of artificial intelligence use definition of consciousness and do not attach this term to a person. They understand by consciousness only ability to cognize the world with the help of thinking and mind.